2011
DOI: 10.1149/1.3577681
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Deposition of Ni/Pt Bi-Layer on Polyimide Film as Flexible Counterelectrodes for Dye-Sensitized Solar Cells

Abstract: A metalized plastic substrate made of a polyimide film coated with a Ni/Pt bi-layer is prepared as counterelectrode for dye-sensitized solar cell (DSSC). Surface metallization of Ni/Pt on polyimide is carried out via a chemical process, where top Pt acts as the catalyst and bottom Ni is the conduction/light-reflection layer. This counterelectrode possesses superior sheet resistance (0.173 X/h) and charge transfer resistance (0.38 X cm2). The DSSC based on this metalized polyimide counterelectrode exhibits an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…188 In addition to PET and PEN, polyimide (PI) can also be used as a polymer substrate owing to its excellent thermal/chemical stability and superior mechanical strength. 189,190 Lin et al deposited a bilayer Ni 3 S 2 /Ni-P film on a PI substrate through a series of chemical/electrochemical processes. 191 The bottom layer Ni-P replaced conventional TCO as a conductive layer, and the top layer Ni 3 S 2 was used as the catalyst for I 3 À reduction.…”
Section: Conductive Substratesmentioning
confidence: 99%
“…188 In addition to PET and PEN, polyimide (PI) can also be used as a polymer substrate owing to its excellent thermal/chemical stability and superior mechanical strength. 189,190 Lin et al deposited a bilayer Ni 3 S 2 /Ni-P film on a PI substrate through a series of chemical/electrochemical processes. 191 The bottom layer Ni-P replaced conventional TCO as a conductive layer, and the top layer Ni 3 S 2 was used as the catalyst for I 3 À reduction.…”
Section: Conductive Substratesmentioning
confidence: 99%
“…The agglomerated Ni nanoparticles were distributed non-uniformly on the PI surface as shown in Figure 8c. It has been reported that the Ni nanoparticle film formed on PI was highly resistive due to a high sheet resistance (109 MΩ/γ) [31]. The Ni nanoparticles within the PAA layer also distributed non-uniformly and their particle sizes were 7.5-19 nm as shown in Figure 8d.…”
Section: Cross-sectional Characterization Of Metallized Pi Filmmentioning
confidence: 88%
“…In contrast, solution-based electrochemical deposition is a cost-effective method. Prior to electrochemical deposition, the inert PI surface needs to be activated/modified by a base treatment of potassium hydroxide (KOH), ion exchange, and catalyst reduction [4,8,10,[27][28][29][30][31][32][33][34]. Pd is a traditional catalyst due to its superior catalytic activity, but is expensive.…”
Section: Metallization Process Of Pimentioning
confidence: 99%
See 1 more Smart Citation
“…The ELD of Ni/P layers is a catalytic reaction that requires either a trace amount of seed Ni [5,6] or noble metals such as palladium [7,8] to lower the activation energy for nucleation and growth. Because the ELD process occurs on the catalyst-attached Si surface, the adhesion of Ni/P films is related to the interfacial properties of the catalyst and Si surface.…”
Section: Introductionmentioning
confidence: 99%